2005
DOI: 10.1159/000086130
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Maternal Nicotine Exposure during Lactation on Breast-Fed Rat Pups

Abstract: Background: Nicotine is known to be associated with adverse effects in infants and children. It is concentrated in breast milk and is absorbed by the infant. The aim of this study was to investigate the effects on breast-fed rat pups of maternal nicotine exposure during lactation. Methods: In the experimental group (n = 6), nicotine was given to lactating dams (2 mg/kg/day) after delivery and continued for 10 days during lactation. Control animals (n = 4) received saline for the same duration. The suckling rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
16
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 41 publications
5
16
0
1
Order By: Relevance
“…This is in accordance with the reports that cigarette smoking results in decreased activities of scavenging enzymes and an inhibition of the enzyme glutathione reductase [24,25]. Supplementation of selenium enhanced the activity of scavenging antioxidant enzymes [26].…”
Section: Discussionsupporting
confidence: 92%
“…This is in accordance with the reports that cigarette smoking results in decreased activities of scavenging enzymes and an inhibition of the enzyme glutathione reductase [24,25]. Supplementation of selenium enhanced the activity of scavenging antioxidant enzymes [26].…”
Section: Discussionsupporting
confidence: 92%
“…This is in accordance with the reports that cigarette smoking results in decreased activities of scavenging enzymes [29,12]. Kalpana and Menon [21] have suggested that superoxide anion and hydrogen peroxide are the main source of nicotine induced free radical production depleting the cellular antioxidants.…”
Section: Discussionsupporting
confidence: 92%
“…The toxic effect of maternal exposure to tobacco smoke on the fetal metabolic status is indicated by the significant disturbance of the antioxidant status in newborns exposed in utero to tobacco smoke [7] . Also, induction of oxidative stress and detrimental histopathological changes have been observed in the lungs and liver of breast-fed rat pups whose mothers were exposed to nicotine [8] .…”
Section: Introductionmentioning
confidence: 99%